The Role of Plasma Transfusion in Massive Bleeding: Protecting the Endothelial Glycocalyx? - Barelli, Stefano; Alberio, Lorenzo (Frontiers in Medicine, 2018)
Massive haemorrhage is a leading cause of death worldwide. During the last decade several retrospective and some prospective clinical studies have suggested a beneficial effect of early plasma-based resuscitation on survival in trauma patients. The underlying mechanisms are unknown but appear to involve the ability of plasma to preserve the endothelial glycocalyx. In this mini-review we summarize current knowledge on glycocalyx structure and function, and present data describing the impact of haemorrhagic shock and resuscitation fluids on glycocalyx. Animal studies show that haemorrhagic shock leads to glycocalyx shedding, endothelial inflammatory changes, and vascular hyper-permeability. In these animal models, plasma administration preserves glycocalyx integrity and functions better than resuscitation with crystalloids or colloids. Additionally, we briefly present data on the possible plasma components responsible for these effects. The endothelial glycocalyx is increasingly recognized as a critical component for the physiological vasculo-endothelial function, which is destroyed in haemorrhagic shock. Interventions for preserving an intact glycocalyx shall improve survival of trauma patients.